Ambition of the Main Character In Nobody Movie Directed by Ilya Naishuller - Unpris Yastanti; Bryan Kalbu Adhi (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2023)
The purposes of the research are to investigate ambition and the characteristics of the main character in Nobody movie directed by Ilya Naishuller. This research used descriptive qualitative method to analyze the data. This research was taken from Nobody Movie. The results of this study show that: (1) The ambition of the main character (Hutch) can be seen in Nobody movie. It happens when Hutch knows the criminals take the cat bracelet of his daughter. His ambition is to protect his family. Hutch will be paying off all the problem and consequences to take any risk by protecting his whole family. He would like to find them and bring it back. He promises. He looks for the criminals, a Russian mafia. He fights and meets the Yulian’s People to revenge. (2) There are 5 characteristics of the ambition in Nobody movie, namely: Achievement Motivation Ambition, Self-Attitude Ambition, Attitude Dominance Ambition, Self-regulation and Attitude Dominance Ambition.